2020
DOI: 10.1007/s00417-020-04894-3
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of oral anticoagulation on success rates and risk of bleeding events after iStent inject implantation combined with phacoemulsification

Abstract: Purpose We conducted a retrospective study to evaluate the intraocular pressure (IOP) lowering effect, the success rates, and the risk of bleeding events of patients receiving an iStent inject combined with phacoemulsification under anticoagulation therapy compared with a matched control group. Methods In this retrospective study, sixty-four eyes underwent an iStent inject implantation combined with phacoemulsification at two centers. Thirty-two eyes received surgery while under anticoagulation therapy, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
3
3
0
Order By: Relevance
“…However, the postsurgical IOP in this study was not affected by the spike as analyzed by the Cox proportional hazard ratio model ( Table 5 ). As was reported previously, 28 effects of postsurgical hyphema and IOP spike may be short and only a minor factor on the final surgical outcome.…”
Section: Discussionsupporting
confidence: 73%
“…However, the postsurgical IOP in this study was not affected by the spike as analyzed by the Cox proportional hazard ratio model ( Table 5 ). As was reported previously, 28 effects of postsurgical hyphema and IOP spike may be short and only a minor factor on the final surgical outcome.…”
Section: Discussionsupporting
confidence: 73%
“…Even though over 30% of included patients were on oral anticoagulation therapy at the time of surgery, we did not see any association between anticoagulation therapy and hyphema, which is in line with previous studies. 20,21 Thus, our results indicate FIGURE 5. Reduction of ≥ 1 medication after 2 years.…”
Section: Discussionsupporting
confidence: 59%
“…However, it recently was reported that these drugs do not interfere with the success rate of iStent inject implantation. 16 Notably, first eyes showed a higher mean baseline IOP than second eyes. The reason for this might be that, if trabecular bypass stent implantation is indicated for both eyes according to our standard operating procedures, surgery is commonly performed for the eye with the higher IOP first, which in turn may be responsible for a higher relative IOP-reduction and, hence, higher success rates.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, six out of all participants were under oral anticoagulation therapy. However, it recently was reported that these drugs do not interfere with the success rate of iStent inject implantation 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation